A novel balance training approach: Biomechanical study of virtual reality-based skateboarding - Kantha, Phunsuk; Hsu, Wei-Li; Chen, Po-Jung; Tsai, Yi-Ching; Lin, Jiu-Jenq (Frontiers in Bioengineering and Biotechnology, 2023)
Abstract Introduction: The use of virtual reality (VR) technology in training and rehabilitation gained increasing attention in recent years due to its potential to provide immersive and interactive experiences. We developed a novel VR-based balance training, VR-skateboarding, for improving balance. It is important to investigate the biomechanical aspects of this training, as it would have benefited both health professionals and software engineers. Aims: This study aimed to compare the biomechanical characteristics of VR-skateboarding with those of walking. Materials and Methods: Twenty young participants (10 males and 10 females) were recruited. Participants underwent VR-skateboarding and walking at the comfortable walking speed, with the treadmill set at the same speed for both tasks. The motion capture system and electromyography were used to determine joint kinematics and muscle activity of the trunk and legs, respectively. The force platform was also used to collect the ground reaction force. Results: Participants demonstrated increased trunk flexion angles and muscle activity of trunk extensor during VR-skateboarding than during walking (p < 0.01). For the supporting leg, participants' joint angles of hip flexion and ankle dorsiflexion, as well as muscle activity of knee extensor, were higher during VR-skateboarding than during walking (p < 0.01). For the moving leg, only hip flexion increased in VR-skateboarding when compared to walking (p < 0.01). Furthermore, participants increased weight distribution in the supporting leg during VR-skateboarding (p < 0.01). Conclusions: VR-skateboarding is a novel VR-based balance training that has been found to improve balance through increased trunk and hip flexion, facilitated knee extensor muscles, and increased weight distribution on the supporting leg compared to walking. These differences in biomechanical characteristics have potential clinical implications for both health professionals and software engineers. Health professionals may consider incorporating VR-skateboarding into training protocols to improve balance, while software engineers may use this information to design new features in VR systems. Our study suggests that the impact of VR-skateboarding particularly manifest when focusing on the supporting leg. Clinical Trial Registration: ClinicalTrials.gov, NCT05375201